O ensino de arte no município de Caxias do Sul: necessidades e estratégias de adaptação dos professores licenciados em música - Geremia, Ians Soares (My University, 2021)
Inspite of the improvement over the time of the educational legislation in Brazil, some laws can still be considered multifaceted, and its ways of interpretation and fulfillment, substantially distinct. Musical teaching and Art discipline have always found themselves imbricated in this process of constant modifications that envolve the different political scenarios experienced throwght this country history. Since the year of 2008, more and more licensed in music teachers began to teach in Art discipline of the regular education. This occurred because of the Law 11.769/08, that made the musical knowledge an obligatory curricular component of the Art discipline and, posteriorly, the Law 12.278/16, wich have especified the four artistic languages (visual arts, music, dance and theater) presents in this discipline. The teachers very often end up needing to cover, in the classroom, the knowledges of the artistic languages of wich they dont have qualification. This work intends to investigate which are the utilized strategies of the teachers licensed in music who work in the city of Caxias do Sul to teach the knowledges of the visual arts, dance and teather languages in Art discipline. The research possessed qualitative focus and was accomplished throught an interview in semi structured format with each one of these teachers. This work is divided in four main parts: the first one estabilishes an analisis of the musical teaching in the institutionalization processs of the education of this country. The second one, also throught a historic perspective and a literature review, intends to discourse about the music teaching in brazilian legislation and its modifications, analizing also the current legislation. The third part, it its turn, conceives a critical posture about some contextual aspects of the current legislation. Lastly, the fourth part discourses about the methodologic principles used in the interview, as well as the obtained results. [resumo fornecido pelo autor]
Apesar de que a legislação educacional tenha se aperfeiçoado ao longo do tempo no Brasil, algumas leis ainda podem ser consideradas multifacetadas, e suas formas de interpretação e cumprimento, substancialmente distintas. O ensino de música e a disciplina Arte sempre se encontraram imbricados nesse processo de mudanças constantes que envolve os diversos cenários políticos vivenciados ao longo da história do país. Desde o ano de 2008, começaram a surgir cada vez mais professores licenciados em música para atuar na disciplina Arte do ensino regular no país. Isto ocorreu em função da Lei 11.769/08, que tornou o ensino de música um componente curricular obrigatório na disciplina Arte, e, posteriormente, a Lei 13.278/16, que especificou as quatro linguagens artísticas (artes visuais, música, dança e teatro) presentes nesta disciplina. Os professores muitas vezes acabam tendo que abarcar, em sala de aula, conhecimentos de linguagens artísticas das quais não possuem formação. Este trabalho busca investigar quais as estratégias utilizadas pelos professores licenciados em música que atuam no município de Caxias do Sul, para ensinar os conhecimentos das linguagens de artes visuais, dança e teatro na disciplina Arte. A pesquisa teve enfoque qualitativo e foi realizada através de uma entrevista em formato semiestruturado com cada um desses professores. Este trabalho está divido em quatro partes principais: a primeira estabelece uma análise do ensino de música no processo de institucionalização da educação no país. A segunda, também através de uma perspectiva histórica e de uma revisão bibliográfica, procura dissertar sobre o ensino de música na legislação brasileira e suas modificações, analisando inclusive a legislação vigente. A terceira parte, por sua vez, concebe uma postura crítica acerca de alguns aspectos contextuais da legislação vigente. Por último, a quarta parte disserta sobre os princípios metodológicos utilizados na entrevista, bem como os resultados obtidos. [resumo fornecido pelo autor]
Keywords: Música na educação; Música - Instrução e estudo; Ensino - Legislação